Virulence Characterization of Listeria monocytogenes, Listeria innocua, and Listeria welshimeri Isolated from Fish and Shrimp Using In Vivo Early Zebrafish Larvae Models and Molecular Study - Arkadiusz Józef Zakrzewski; Wioleta Chajęcka-Wierzchowska; Anna Zadernowska; Piotr Podlasz (Pathogens, 2020)
Listeriosis is one of the most notable foodborne diseases and is characterized by high rates of mortality. L. monocytogenes is the main cause of human listeriosis outbreaks, however, there are isolated cases of disease caused by other species of the genus Listeria. The aim of this study was to evaluate strains of L. monocytogenes (n = 7), L. innocua (n = 6), and L. welshimeri (n = 2) isolated from fish and shrimps for their virulence based on the presence of virulence genes and the in vivo Danio rerio (zebrafish) larvae models. A total of 15 strains were analyzed. The zebrafish larvae model showed that the larvae injected with L. monocytogenes strains were characterized by the lowest survival rate (46.5%), followed by L. innocua strains (64.2%) and L. welshimeri (83.0%) strains. Multiplex PCRs were used for detection of selected virulence genes (luxS, actA2, prfA, inlB, rrn, iap, sigB, plcB, actA, hlyA), the majority of which were present in L. monocytogenes. Only a few virulence-related genes were found in L. welshimeri, however, no correlation between the occurrence of these genes and larval survival was confirmed. This research highlights the importance of the potential impact that Listeria spp. strains isolated from fish and shrimps may have on consumers.